Hadith #557 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
`Aisha said, “Once Allah’s Messenger (ﷺ) delayed the `Isha’ prayer till `Umar reminded him by saying, “The prayer!” The women and children have slept. Then the Prophet (ﷺ) came out and said, ‘None amongst the dwellers of the earth has been waiting for it (the prayer) except you.” `Urwa said, “Nowhere except in Medina the prayer used to be offered (in those days).” He further said, “The Prophet (ﷺ) used to offer the `Isha’ prayer in the period between the disappearance
Grade: Sahih

Hadith #1311 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
The funeral prayer should be offered for every child even if he were the son of a prostitute as he was born with a true faith of Islam (i.e. to worship none but Allah Alone). If his parents are Muslims, particularly the father, even if his mother were a non-Muslim, and if he after the delivery cries (even once) before his death (i.e. born alive) then the funeral prayer must be offered. And if the child does not cry after his delivery (i.e. born dead) then his funeral prayer should not be offered
Grade: Sahih

Hadith #1603 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
Salim said, “In the year when Al-Hajjaj bin Yusuf attacked Ibn Az-Zubair, the former asked ‘Abdullah (Ibn ‘Umar) what to do during the stay on the Day of ‘Arafa (9th of Dhul-Hajjah). I said to him, “If you want to follow the Sunna (the legal way of the Prophet (ﷺ)) you should offer the Salat just after midday on the Day of the ‘Arafa. ‘Abdullah bin ‘Umar said, ‘He (Salim) has spoken the truth.’ ” They (the Companions of the Prophet (ﷺ)) used to offer the Zuhr and Asr p
Grade: Sahih

Hadith #2096 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
that Malik bin Aus said, “I was in need of change for one-hundred Dinars. Talha bin ‘Ubaidullah called me and we discussed the matter, and he agreed to change (my Dinars). He took the gold pieces in his hands and fidgeted with them, and then said, “Wait till my storekeeper comes from the forest.” `Umar was listening to that and said, “By Allah! You should not separate from Talha till you get the money from him, for Allah’s Messenger (ﷺ) said, ‘The selling of gold for gold is Riba
Grade: Sahih

Hadith #2118 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
If somebody bought fruits before their benefit is evident and then the fruits were spoiled with blights, the loss would be suffered by the owner (not the buyer). Narrated Salim bin ‘Abdullah from Ibn Umar: Allah’s Messenger (ﷺ) said, “Do not sell or buy fruits before their benefit was evident and do not sell fresh fruits (dates) for dried dates.”
Grade: Sahih

Hadith #2525 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
Anas bin Malik said, “When the emigrants came Medina, they had nothing whereas the Ansar had land and property. The Ansar gave them their land on condition that the emigrants would give them half the yearly yield and work on the land and provide the necessaries for cultivation.” His (i.e. Anas’s mother who was also the mother of `Abdullah bin Abu Talha, gave some date-palms to Allah’ Apostle who gave them to his freed slave-girl (Um Aiman) who was also the mother of Usama bin Zaid. When
Grade: Sahih

Hadith #3088 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
Once `Umar bin `Abdul `Aziz delayed the `Asr prayer a little. `Urwa said to him, “Gabriel descended and led the prayer in front of the Prophet (ﷺ) ” On that `Umar said, “O `Urwa! Be sure of what you say.” “Urwa, “I heard Bashir bin Abi Masud narrating from Ibn Masud who heard Allah’s Messenger (ﷺ) saying, ‘Gabriel descended and led me in prayer; and then prayed with him again, and then prayed with him again, and then prayed with him again, and then prayed with him again, coun
Grade: Sahih

Hadith #3845 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
I asked Al-Husain bin Muhammad who was one of the sons of Salim and one of the nobles amongst them, about the narration of Mahmud bin Ar-Rabi ‘from `Itban bin Malik, and he confirmed it.
Grade: Sahih

Hadith #3859 - Sahih al-Bukhari - Ibn Shihab from `Urwa (Sahih al-Bukhari)
These were the battles of Allah’s Messenger (ﷺ) (which he fought), and while mentioning (the Badr battle) he said, “While the corpses of the pagans were being thrown into the well, Allah’s Messenger (ﷺ) said (to them), ‘Have you found what your Lord promised true?” `Abdullah said, “Some of the Prophet’s companions said, “O Allah’s Messenger (ﷺ)! You are addressing dead people.’ Allah’s Messenger (ﷺ) replied, ‘You do not hear what I am saying, better than they.’
Grade: Sahih